IONIC CONSTITUENTS IN AEROSOL PARTICLES AT SYOWA STATION, EAST ANTARCTICA, DURING 1996 - オサダ, カズオ; ハヤシ, マサヒコ; ウイ, ヒロタカ; イワサカ, ヤスノブ; OSADA, Kazuo; HAYASHI, Masahiko; UI, Hirotaka; IWASAKA, Yasunobu (National Institute of Polar Research, 1998)
P(論文) This preliminary study was conducted as part of an atmospheric aerosol monitoring program at Syowa Station, East Antarctica. Atmospheric aerosol particles were collected at Syowa Station from April 1996 to January 1997 using a cascade impactor. Although aerosols were collected on selected and limited days of the year, concentrations of CH_3SO_3 and nssSO_4^2 showed distinct summer maxima. Concentration levels of sea-salt components were sporadically high in winter to spring. NO_3 and C_2O_4^2 concentrations were high in spring but long-term data are needed to obtain statistically significant seasonal variations. Results of size-fractionated aerosol samples suggest that sea-salt particles in spring and early summer were more depleted for a coarse fraction (>2μm diameter) than in winter. CH_3SO_3 and nssSO_4^2 were predominantly found in submicron aerosols whereas the average size fraction of NO_3 through the observation period was 20% for >2μm, 50% for 2 to 0.2μm and 30% for <0.2μm diameter. departmental bulletin paper